Analisis dan Perancangan Sistem Informasi Akuntansi Penjualan dan Persediaan - Henny Hendarti; Anton Anton; Didi Didi; Mochtar Cakra (The Winners, 2008)
Article purpose was to make computerized system useable for running the company operational and the activity always needs information. The data collecting method were done by literature study, field study, and documentation study. Analysis and design method consisted of four phase, which were investigation system, analysis system, design system, and implementation system. The result from observation was the company needs transaction recording system that computerized so every selling or buying transaction of foreign currency can directly update the inventory. The conclusion is that the up-to-date selling and inventory information can help manager in making decision.